Balance between Interleukin-18 and Interleukin-18 binding protein in auto-inflammatory diseases. (February 2022) - Harel, Mathilde; Fauteux-Daniel, Sébastien; Girard-Guyonvarc'h, Charlotte; Gabay, Cem
Abstract: Interleukin (IL)-18 is a member of the IL-1 family of cytokines with pleiotropic and potent pro-inflammatory activities that are tightly controlled at the level of production and in the extracellular space. Indeed, IL-18 is translated as a leaderless biologically inert pro-peptide that is cleaved by caspase-1 in its N-terminus domain to become active. Mature Il-18 is then released out of the cells via a phenomenon of inflammatory cell death termed pyroptosis. The biological activity of IL-18 is also regulated by a naturally-occurring soluble inhibitor, IL-18 binding protein (IL-18BP) that binds IL-18 and forms high affinity complexes, thus preventing IL-18 to signal through its cell surface receptors. IL-18BP is present in high amount in the circulation, thus unbound free Il-18 is virtually absent in normal and most pathological conditions. Recent findings showed that IL-18 is present in remarkably high concentrations in some autoinflammatory diseases, including adult-onset Still's disease, systemic juvenile idiopathic arthritis and in various conditions associated with hemophagocytic lymphohistiocytosis/macrophage activation syndrome. Furthermore, elevated levels of free IL-18 are present in correlation with clinical and biological signs of disease activity. Most importantly, some patients with these diseases responded remarkably well to the administration of recombinant human IL-18BP, further indicating the pathogenic role of Il-18 and providing a strong rational for the use of IL-18 inhibitors in some of these difficult to treat auto-inflammatory diseases.